Pengaruh Media Tanam dan Pupuk Kompos Kotoran Sapi Terhadap Pertumbuhan Tanaman Jahe (Zingiber officinale) - Permadi, Mhd Bambang; Amrul, Hanifah Mutia Zaida Ningrum; Siswanto, Yudi (JURNAL AGROPLASMA, 2024)
Ginger contains a number of phenolic compounds that are antioxidants, which are thought to protect cells from damage. The use of organic fertilizers on agricultural land has existed since ancient times by utilizing natural materials. The advantage of cocopeat for planting media is that it can store water or maintain the humidity of the planting media. The purpose of this study was to determine the effect of providing planting media and cow dung compost and the interaction of providing planting media and cow dung compost on the growth of ginger plants (Z. officinale). This research was conducted on the land of the LLDIKTI REGION 1 SUMUT Office, Jalan Sempurna no. 8, Tanjung Sari Village, Medan Selayang District, Medan City, North Sumatra. The research time was carried out for approximately 3 months starting from March 2024 to July 2024. This study used a factorial Randomized Block Design (RAK) consisting of 2 treatment factors with 16 treatment combinations with 3 repetitions so that 48 plots were obtained with the number of plants/plot of 4 plants. So the total sample plants are 192 sample plants. Factor I is the provision of Cow Manure Compost with the symbol "K" consisting of 4 levels, namely: K0 = 0 kg / plot, K1 = 1 kg / plot, K2 = 2 kg / plot, K3 = 3 kg / plot. Factor II is the provision of rice husks with the symbol "M" consisting of 4 levels, namely: M0 = 100% topsoil, M1 = 50% topsoil + 50% rice husks, M2 = 50% topsoil + 50% rice husk charcoal, M3 = 50% topsoil + 50% cocopeat. The results of the study showed that the provision of planting media and cow dung compost fertilizer was significantly different from the age of shoot emergence, number of shoots, stem diameter and rhizome weight per sample. for the largest rhizome found in K3 = 3 kg/plot, namely 23.88 g, which is not significantly different from the treatment K2 = 2 kg/plot, namely 20.69 g, but significantly different from the treatment K1 = 1 kg/plot, namely 14.21 g, but very significantly different from the treatment K0 = 0 kg/plot, namely 5.69 g Keywords: ginger, cow dung, planting media